Almost a chest hit: An aurochs humerus with hunting lesion from Göbekli Tepe, south-eastern Turkey, and its implications. (30th November 2018) - Pöllath, Nadja; Dietrich, Oliver; Notroff, Jens; Clare, Lee; Dietrich, Laura; Köksal-Schmidt, Çiğdem; Schmidt, Klaus; Peters, Joris
Abstract: An aurochs right humerus with a fragment of an embedded projectile point was discovered during excavations at early Neolithic Göbekli Tepe in south-eastern Turkey. Evidence for hunting trauma in bones is extremely rare in the prehistoric record from the Near East and Africa, while the dataset from Europe is much larger. In this contribution a hunting lesion from Göbekli Tepe and its context will be described and discussed against the background of data on similar hunting lesions found in Europe, the Near East and Africa. Communal hunting is identified as one strategy to hunt down large game like aurochs, which, in the case of Göbekli Tepe, will be placed in the socio-cultural context of large scale gatherings.